2011
DOI: 10.1088/0954-3899/38/8/085104
|View full text |Cite
|
Sign up to set email alerts
|

Fragment mass distributions in the fission of heavy nuclei by intermediate- and high-energy probes

Abstract: Recent experiments have shown that the multimode approach for describing the fission process is compatible with the observed results. A systematic analysis of the parameters obtained by fitting the fission-fragment mass distribution to the spontaneous and low-energy data has shown that the values for those parameters present a smooth dependence upon the nuclear mass number. In this work, a new methodology is introduced for studying fragment mass distributions through the multimode approach. It is shown that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
13
0
6
Order By: Relevance
“…Also, as shown in Figure 3, the excitation energy of the fissioning nuclei are in many cases around hundreds of MeV, and the parameters are not determined at these energies. In the present work we extend the analysis performed in Ref [17] and discuss also the possibility of symmetric fission dominance at high energies. It was believed that at low energies fission should be predominantly asymmetric, while at high energies the symmetric mode should be dominant because at these energies the effects due to nuclear structure would be washed out.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Also, as shown in Figure 3, the excitation energy of the fissioning nuclei are in many cases around hundreds of MeV, and the parameters are not determined at these energies. In the present work we extend the analysis performed in Ref [17] and discuss also the possibility of symmetric fission dominance at high energies. It was believed that at low energies fission should be predominantly asymmetric, while at high energies the symmetric mode should be dominant because at these energies the effects due to nuclear structure would be washed out.…”
Section: Introductionsupporting
confidence: 54%
“…In recent papers [17,18] we discussed about the effects of the mass-and energy-distributions on the final fragment mass distributions. We have shown that in fission induced by high energy probes, as protons and photons, the fissioning nuclei are quite different from the target nucleus due to the emission of particles during intranuclear cascade and during the evaporation steps before fission occurs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both intranuclear cascade and evaporation/fission calculations with the CRISP model have been extensively investigated yielding good results for reactions induced by photons, electrons and protons and observables such as neutron or proton multiplicity, fission and spallation cross sections, and fragment mass distributions [14,16,17,[22][23][24][25][26][27].…”
Section: Modelmentioning
confidence: 99%